Assessment of anthropometry, academic performance and absenteeism in a comprehensive educational programme on the Cape Flats : a cross-sectional survey with a cohort analysis - Kamminga, Froukje (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references (leaves 72-73).